2011
DOI: 10.1016/j.procbio.2010.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Study on the microalgal pigments extraction process: Performance of microwave assisted extraction

Abstract: The performance of microwaves irradiation (MAE and VMAE) to extract pigments from two marine microalgae was compared to conventional processes (cold and hot soaking and ultrasound-assisted extraction). Pigments were quantified by RP-HPLC and extraction performance was assessed regarding rapidity, reproducibility and extraction yields. Scanning electron microscopy was used at all extraction steps to assess the impact of the process on microalgal cell integrity. Freeze-drying and pigments extraction preserved mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
166
2
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 308 publications
(189 citation statements)
references
References 37 publications
(40 reference statements)
3
166
2
5
Order By: Relevance
“…Furthermore, there are several suitable solvents that meet the requirements and regulations of the food and feed sectors. Other extraction techniques, which have already been described for the extraction of plant biomass, including ultrasound-assisted extraction (UAE), pulsed electric field extraction (PEF) and microwave-assisted extraction (MAE), are also at the focus of current research in order to adapt them for microalgae treatment (Parniakov et al 2015;Pasquet et al 2011;Plaza et al 2012). …”
Section: Cascaded Extractionmentioning
confidence: 99%
“…Furthermore, there are several suitable solvents that meet the requirements and regulations of the food and feed sectors. Other extraction techniques, which have already been described for the extraction of plant biomass, including ultrasound-assisted extraction (UAE), pulsed electric field extraction (PEF) and microwave-assisted extraction (MAE), are also at the focus of current research in order to adapt them for microalgae treatment (Parniakov et al 2015;Pasquet et al 2011;Plaza et al 2012). …”
Section: Cascaded Extractionmentioning
confidence: 99%
“…Besides the purification of antiproliferative pigments [5,6], additional studies established that multiple cellular and molecular processes are affected by microalgae carotenoids. It was first demonstrated that their antioxidant activity protects against ROSinduced DNA mutations, and tissue and animals studies confirmed that most carotenoids effectively reduce the inflammatory processes initiated by carcinogenic agents, and thus prevent the risk of cancer initiation.…”
Section: Beyond Their Major Ecolophysiological Functions Phytoplanktmentioning
confidence: 99%
“…This latter aim requires that the basic structure of the extracted particles be stiff. Vegetal cells generally feature a stiff structure; microalgae lacking frustule or thick outer exopolysaccharide envelope may not benefit from microwave-assisted extraction (Pasquet et al, 2011), while wall-possessing microalgae benefit greatly from it (yields 3x-5x in a fraction of the time; Cravotto et al, 2008). Microwave assisted extraction may be carried out in closed and open systems (Figure 7).…”
Section: Optimisation Of Microwave-assisted Extraction (Mae)mentioning
confidence: 99%